Impedance spectroscopy of composites based on porous silicon and silica aerogel for sensor applications - Karlash, A.Yu.; Kuznetsov, G.V.; Milovanov, Yu.S.; Skryshevsky, V.A. (Functional Materials, 2013)
Electrophysical and optical properties of heterogeneous composite systems based on nanosilicon (nc–Si) and silica aerogel (SiOx) powders have been investigated using impedance spectroscopy and FTIR spectroscopy methods. In FTIR transmittance spectra the presence of vibration modes of hydroxyl groups covering the internal surface of SiOx matrix as well as associated Si–OH groups has been revealed that should determine the sensing behavior of considered composites mainly under water treating. Based on impedance measurements possible mechanisms of charge carrier transport have been proposed. It was shown that the main process in carrier transport of pressed SiOx/nc–Si composite structures is the percolation tunneling of charge carriers through the silicon nanoclusters system. The dynamic interaction of composite structures with water molecules and pure ethyl alcohol has been investigated. It was revealed that desorption kinetics of SiOx/nc–Si nanocomposites are characterized by higher desorption rate compared to SiOx samples. The relative change of resistance value under water treating ΔR/R ≅ 0.99 was almost similar for all investigated samples that confirmed the crucial role of oxide matrix in adsorption-desorption processes of considered composite structures. It was concluded that such sensing behavior could be utilized for construction the chemical sensors of humidity and alcohol based on porous SiOx and SiOx/nc–Si nanocomposites.